Toward a Worldview for Civilizational Development: A Study of the Islamic Worldview - Berghout, Abdelaziz (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Toward a Worldview for Civilizational Development: A Study of the Islamic Worldview